Effective cryopreservation protocol for preservation of male primate (Macaca fascicularis) prepubertal fertility. Issue 6 (December 2020) - Jung, Sang-Eun; Ahn, Jin Seop; Kim, Yong-Hee; Kim, Bang-Jin; Won, Jong-Hyun; Ryu, Buom-Yong
Highlights: Higher recovery of SSC is a key factor for effective freezing protocol. Testicular tissue freezing is more effective than single cell suspension freezing. Trehalose 200 mmol/l improves the effectiveness of testicular tissue freezing. Successful primate SSC colony formation was observed by xenotransplantation. Abstract: Research question: Can specimen types (cells versus tissues) and additive cryoprotectant agents contribute to efficient cryopreservation of primate spermatogonial stem cells (SSC)? Design: Testicular tissues or cells from four prepubertal monkeys were used in this study. The freezing efficacy of testicular tissue was compared with cell suspensions using conventional freezing media (1.4 mol/l dimethyl sulfoxide [DMSO]) and the efficacy of cryoprotectant additives (1.4 mol/l DMSO combined with trehalose 200 mmol/l, hypotaurine 14 mmol/l, necrostatin-1 50 µmol/l or melatonin 100 µmol/l) was evaluated in testicular tissue freezing. Results: The survival rate (46.0 ± 4.8% versus 33.7 ± 6.0%; P = 0.0286) and number of recovered cells (5.0 ± 1.5 × 10 6 cells/g versus 0.7 ± 0.8 × 10 6 cells/g; P = 0.0286) were significantly higher in frozen tissues than in frozen cell suspensions. After tissue freezing, a higher number of recovered PGP9.5 + cells were observed with 200 mmol/l trehalose treatment than in DMSO controls (2.4 ± 0.6 × 10 6 cells/g versus 1.1 ± 0.3 × 10 6 cells/g; P = 0.0164). Normal establishment of donor-derived colony was observed in SSC after tissue freezing with 200 mmol/l trehalose. Conclusions: Testicular tissue freezing is more effective than single cell suspension freezing for higher recovery of undifferentiated spermatogonia. Moreover, it was verified that slow freezing using 200 mmol/l trehalose, 1.4 mol/l DMSO and 10% KnockOut™ Serum Replacement in Dulbecco's phosphate-buffered saline is an effective cryopreservation protocol for primate testicular tissue.